2020
DOI: 10.1186/s13048-020-00735-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective effects of plasma derived from mice of different ages and genders on ovarian failure after cyclophosphamide treatment

Abstract: Background Premature ovarian failure is one of the major side effects of chemotherapy drugs. Blood plasma contains several factors that might lead to the repair of different tissues. Objective The chemoprotective effects of plasma derived from mice with different ages and genders were assessed on ovarian tissue in cyclophosphamide-treated mice. Methods Forty-two adult female mice were divided into six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(77 reference statements)
3
4
0
Order By: Relevance
“…In the uterus, epithelial degeneration, vacuoles within the epithelial lining, decreased glandular proliferation, and increased stromal brous tissue. Similar results were previously reported in rats [18,31] and mice [32]. This side effect of CP is linked to the follicle atresia and granulosa cell apoptosis [33].…”
Section: Discussionsupporting
confidence: 89%
“…In the uterus, epithelial degeneration, vacuoles within the epithelial lining, decreased glandular proliferation, and increased stromal brous tissue. Similar results were previously reported in rats [18,31] and mice [32]. This side effect of CP is linked to the follicle atresia and granulosa cell apoptosis [33].…”
Section: Discussionsupporting
confidence: 89%
“…Bahmanpour and her coworkers explained that primordial and preantral follicles were more sensitive to one single dose of 150 mg/kg CPA administration in their animal model (19). Previous reports have shown that the preantral follicles, as the sensitive ones, may be affected by chemotherapy drugs easily (19,25,26) that is in consistent with our results. The investigation of ovarian morphological for different doses showed that CPA dose of 50 mg/kg had the most remarkable decrease in the number of primordial, primary, preantral and graa an follicles.…”
Section: Discussionsupporting
confidence: 93%
“…Bedoschi et al demonstrated that the primordial and preantral follicles are more susceptible to atresia compared to the antral and graa an follicles (13). Bahmanpour and her coworkers explained that primordial and preantral follicles were more sensitive to one single dose of 150 mg/kg CPA administration in their animal model (19). Previous reports have shown that the preantral follicles, as the sensitive ones, may be affected by chemotherapy drugs easily (19,25,26) that is in consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When a cavity filled with follicular fluid forms, this is called the antral follicle. Depending on the species, folliculogenesis completes one or more follicles and ovulation occurs, but the remaining follicles are involved in the growth process, and suffer from atresia ( Mesbah et al ., 2018 ; Green & Shikanov, 2016 ; West et al ., 2007 ; Bahmanpour et al ., 2020 ). Folliculogenesis and oogenesis are controlled by complicated paracrine, autocrine and juxtacrine genetic factors, and are vital to sustainable fertility ( Dehghani et al ., 2018 ; Matzuk & Burns, 2012 ; Richards & Ascoli, 2018 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%